A novel Nd3+‐doped MgO‐Al2O3‐SiO2‐based transparent glass‐ceramics: Toward excellent fluorescence properties. Issue 7 (25th January 2019) - Han, Lei; Li, Cui; Lin, Chang‐wei; Liu, Jian‐lei; Wu, Jia‐qi; Gui, Hua; Zhang, Qian; Luo, Zhi‐wei; Liu, Tao‐yong; Lu, An‐xian
Abstract: Generally, glass‐ceramics have superior properties compared to their parent glasses. Here, we prepared a novel Nd 3+ ‐doped MgO‐Al2 O3 ‐SiO2 ‐based transparent glass‐ceramics with excellent fluorescence properties. The effects of Nd2 O3 content on the structure and properties of glass‐ceramics were studied, aiming to provide a key guidance for preparing this transparent glass‐ceramics. The results revealed that the glass stability increased originally and then decreased with increasing Nd2 O3 content, so did the variation of wavenumbers in infrared spectra. And these glass‐ceramics are mainly composed of cordierite with residual glassy phase. The three phenomenological intensity parameters (Ω2, 4, 6 ) and radiative properties were estimated by Judd‐Ofelt theory, and the values of Ω2 first decreased and then increased with increasing Nd2 O3 content. Three main emission peaks ascribed to the transitions from 4 F3/2 to 4 I9/2, 4 I11/2, 4 I13/2 at 898, 1057, 1330  nm were observed, respectively. The branching ratios for 4 F3/2 → 4 I11/2 transition increased as the Nd2 O3 content raised, and the fluorescence lifetimes of the 4 F3/2 level were found to increase first and then decrease with Nd2 O3 content (from 181 to 726 μs). The excellent fluorescence properties indicate that this novel glass‐ceramics can be used as a potential solid‐state optical functional material for 1.06 μm laser emission.